Mono or Dual Antiplatelet Therapy for Treating Patients with Peripheral Artery Disease after Lower Extremity Revascularization: A Systematic Review and Meta-Analysis - Shang-Yu Tsai; Ying-Sheng Li; Che-Hsiung Lee; Shion-Wei Cha; Yao-Chang Wang; Ta-Wei Su; Sheng-Yueh Yu; Chi-Hsiao Yeh (Pharmaceuticals, 2022)
The efficacy of dual antiplatelet therapy (DAPT) for patients with peripheral artery disease (PAD) after lower-limb intervention remains controversial. Currently, the prescription of DAPT after an intervention is not fully recommended in guidelines due to limited evidence. This study compares and analyzes the prognosis for symptomatic PAD patients receiving DAPT versus monotherapy after lower-limb revascularization. Up to November 2021, PubMed/MEDLINE, Embase, and Cochrane databases were searched to identify studies reporting the efficacy, duration, and bleeding complications when either DAPT or monotherapy were used to treat PAD patients after revascularization. Three randomized controlled trials and seven nonrandomized controlled trials were included in our study. In total, 74,651 patients made up these ten studies. DAPT in PAD patients after intervention was associated with lower rates of all-cause mortality (HR = 0.86; 95% CI, 0.79–0.94; p < 0.01), major adverse limb events (HR = 0.60; 95% CI, 0.47–0.78; p < 0.01), and major amputation (HR = 0.78; 95% CI, 0.64–0.96) when follow-up was for more than 1-year. DAPT was not associated with major bleeding events when compared with monotherapy (OR = 1.22; 95% CI, 0.69–2.18; p = 0.50) but was associated with a higher rate of minor bleeding as a complication (OR = 2.54; 95% CI, 1.59–4.08; p < 0.01). More prospective randomized studies are needed to provide further solid evidence regarding the important issue of prescribing DAPT.